1966
DOI: 10.1029/jz071i003p00727
|View full text |Cite
|
Sign up to set email alerts
|

Lower ionosphere at solar minimum

Abstract: Two Nike‐Apache rockets were launched in 1964 to measure: (a) positive ion density (N+) with an altitude resolution of approximately 10 meters by use of a modified Gerdien condenser, (b) electron density by radio‐propagation techniques, and (c) the optical depth of solar radiation absorbed in the 60–120 km region with a photoelectron retarding potential analyzer. The flights took place at a time when the intensities of important portions of the solar spectrum were being measured simultaneously from a satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…] Thus, to some extent it is possible to study directly the electron density dependence on ion production. We know, for example, that the normal daytime E region is produced by solar X rays and UV light, and Figure 1 shows a plot of the measured diurnal variation of the peak electron density versus ion production computed using published radiation intensities and ionization cross sections [Bourdeau et al, 1966] standard atmosphere. The electron densities and the radiation data both refer to sunspot minimum conditions.…”
Section: The Dependence Of Electron Density On Ion Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…] Thus, to some extent it is possible to study directly the electron density dependence on ion production. We know, for example, that the normal daytime E region is produced by solar X rays and UV light, and Figure 1 shows a plot of the measured diurnal variation of the peak electron density versus ion production computed using published radiation intensities and ionization cross sections [Bourdeau et al, 1966] standard atmosphere. The electron densities and the radiation data both refer to sunspot minimum conditions.…”
Section: The Dependence Of Electron Density On Ion Productionmentioning
confidence: 99%
“…This model deals with two types of positive ions, one with a small and one with a large recombination rate, the production of the latter being proportional to the concentration of our knowledge of the production mechanisms it seems probable that the lower D region, or C layer, is produced by galactic cosmic rays, even though the expected latitudinal variation of production from this source has not been confirmed. The middle D region is produced by solar hydrogen Lyman-a ionizing nitric oxide, and the region above 80 km mainly by solar X rays and Lyman-/• radiation [Bourdeau et al, 1966]. The steep ledge is most likely caused by an abrupt change with height in the effective electron loss rate [Reid, 1970].…”
Section: The Dependence Of Electron Density On Ion Productionmentioning
confidence: 99%
“…Lyman-alpha fluxes near solar minimum have been tabulated for several rocket experiments by Weeks [ 1967]. Bourdeau et al [1966] found that the regions 83-88 km and 88-93 km are sequentially ionized by 2-8 A X radiation and by the CVI line at 33.7 A that produce O2* and N2* ions. Jayararn and Chin [1967] presented an analytical study of the D-region response to solar flare X radiation.…”
Section: D-region Theorymentioning
confidence: 99%
“…The wave electric field intensity, reflection, transmission and conversion coefficients are derived directly from the basic equations in a plasma and they are numerically calculated by using the value of the ionospheric D layer (BoURDEAU et al, 1965(BoURDEAU et al, , 1966. Discussions are also made on the effect of collision, wave reflection and transmission characteristics and the transition from the anisotropic to the isotropic medium of the ionosphere.…”
Section: Introductionmentioning
confidence: 99%